2019
DOI: 10.1016/j.sigpro.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Robust semi-parametric multiple change-points detection

Abstract: This paper is dedicated to define two new multiple change-points detectors in the case of an unknown number of changes in the mean of a signal corrupted by additive noise. Both these methods are based on the Least-Absolute Value (LAV) criterion. Such criterion is well known for improving the robustness of the procedure, especially in the case of outliers or heavy-tailed distributions. The first method is inspired by model selection theory and leads to a data-driven estimator. The second one is an algorithm bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The heuristic slope procedure has been introduced in [1]. It was applied in the three previous framework (see respectively [4] or [35], [6] and [5]) for deducing a data-driven penalization. In the sequel we detail the case of long-memory change detection.…”
Section: An Adaptive Penalization: the Slope Heuristic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The heuristic slope procedure has been introduced in [1]. It was applied in the three previous framework (see respectively [4] or [35], [6] and [5]) for deducing a data-driven penalization. In the sequel we detail the case of long-memory change detection.…”
Section: An Adaptive Penalization: the Slope Heuristic Proceduresmentioning
confidence: 99%
“…be an estimator of the number of changes using the data-driven procedure. we have shown that this data-driven procedure leads to more accurate results than the procedures based on penalization with a sequence (κ n ) chosen a priori (see in [4] and [35] for the result for Framework 1, [6] for Framework 2, and [5] for the case of Framework 3). In the research about the autonomous vehicles, the cost of a high performance GPS is a problem and a solution proposed is to study the environment of the vehicles to guide the latter in the case of regular trips.…”
Section: An Adaptive Penalization: the Slope Heuristic Proceduresmentioning
confidence: 99%
“…Its two main advantages are, first, that it does not require strong moment conditions to converge or to be asymptotically Gaussian, and second, that it is significantly more robust (see for instance [9]), especially to the presence of possible outliers. It has for example been studied in the context of the detection of breaks in [4] and [2] (for shifts) and [5] (for linear models), for the estimation of parameters of time series, as in [7] (for ARMA processes) or in [1] (for affine causal processes). It also opens the way to more complex procedures, such as robust regression with Huber function (see [8]) or quantile regression (see [11]).…”
Section: Introductionmentioning
confidence: 99%